776 Nanotoxicity of titanium nanosheets for human immune cells. (24th April 2018) - Nishimura, Y; Yoshioka, D; Kumagai-Takei, N; Matsuzaki, H; Lee, S; Yoshitome, K; Otsuki, T
Abstract : Introduction: The characteristic toxicity of nano-scaled materials, that is nanotoxicity, is a recent problem arising in association with nanotechnology. Titanium nanosheets (TNS) are known as 2D materials composed of titanium and oxygen with very thin structure and expected to be valuable for industrial usage. The present study examined the effect of exposure to TNS on human immune cells. Methods: Human peripheral blood mononuclear cells (PBMC) or magnetically isolated CD14 + monocyte or CD4 + T cells were cultured with TNS. Apoptosis was assayed by flow cytometry with annexin V staining. Intracellular microstructures of monocytes were observed by TEM and SEM, and titanium was identified by energy dispersion type X-ray spectroscopy (EDX). Adherent monocytes were pre-cultured with Alexa 568 dextran (A-Dex) to visualise endosomes. Results: TNS exposure induced apoptosis of PBMC in the 7 days culture, the dose dependency of which was similar to asbestos, although apoptosis was not induced at the early stage of day 2 unlike asbestos. The apoptosis was inhibited by Q-VD-OPh pan-caspase inhibitor. Isolated CD4 + T cells as well as monocytes showed apoptosis caused by TNS exposure, whereas monocytes showed giant vacuole formation prior to apoptosis. TNS-like compounds in vacuoles were observed by TEM, and SEM images showed rough surface of the inner layer of vacuolar membrane, in which titanium was identified by EDX. Most of vacuoles showed co-localization with fluorescence of A-Dex. Conclusion: These results indicate that TNS have toxic effect to cause caspase-dependent apoptosis of immune cells. In particular, TNS showed characteristic toxicity for monocytes, in which engulfed TNS were thought to enter into the endosomal pathway, leading to vacuole formation followed by apoptosis. Those findings suggest hazardous risk of occupational exposure to TNS.